2009
DOI: 10.1111/j.1440-1843.2009.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral N‐acetylcysteine attenuates pulmonary emphysema and alveolar septal cell apoptosis in smoking‐induced COPD in rats

Abstract: NAC attenuates lung damage, pulmonary emphysema and alveolar septal cell apoptosis by partly reversing the decrease in VEGF secretion and VEGFR2 protein expression in smoking-induced COPD in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 23 publications
12
39
0
Order By: Relevance
“…Morphological changes such as denudation of endothelium and endothelial cell apoptosis as well as functional alterations have been observed in the pulmonary vasculature in patients with COPD and experimental emphysema animal models (11)(12)(13). Consistent with this concept, evidenced such proposals in cell level, the current study demonstrated that CSE indeed induced the apoptotic cell deaths in ECV304 cells in means of dose-dependent and time-dependent manners.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Morphological changes such as denudation of endothelium and endothelial cell apoptosis as well as functional alterations have been observed in the pulmonary vasculature in patients with COPD and experimental emphysema animal models (11)(12)(13). Consistent with this concept, evidenced such proposals in cell level, the current study demonstrated that CSE indeed induced the apoptotic cell deaths in ECV304 cells in means of dose-dependent and time-dependent manners.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to the well-known mechanisms in which the chronic inflammation of airways, extracellular matrix destruction and oxidative stress are thought to contribute to the pathogenesis of COPD (3), the apoptosis of structural cells in the lung is recently suggested to be an important upstream event in the pathogenesis of COPD (4)(5)(6)(7)(8)(9). Our previous studies demonstrated that the apoptosis was involved in both alveolar epithelial cells and endothelial cells in the parenchyma of COPD and that the apoptotic cells were increased in emphysematous lung parenchyma in both animal model and patients (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, we only appreciated a significant reduction at 10 m M , the highest concentration assayed, which was also in accordance with previous studies [47]. Recent studies have shown that NAC may ameliorate lung emphysema induced by elastase or cigarette smoke in animal models [49,50], which indicates that an active antioxidant therapy could be useful to ameliorate the emphysema progression in humans. Since neutrophil apoptosis resistance is a marker of neutrophil activation and oxidative stress and chronic inflammation increase neutrophil survival, it would be expected that NAC prevents apoptosis resistance.…”
Section: Discussionsupporting
confidence: 77%
“…We found that SOD mimetic was more efficacious than NAC in attenuating elastase-induced airspace enlargement and lung function decline in WT mice. This is corroborated by the studies that show a slight protective effect of NAC against rat emphysema induced by elastase and CS exposure (48,49). Interestingly, SOD mimetic, but not NAC, exhibited a protective effect on elastase-induced emphysematous changes in SOD3 KO mice.…”
Section: Discussionsupporting
confidence: 70%